The Tribadism of Philaenis in Martial: another possible interpretation of the epigram 9.40 - Mañas Núñez, Manuel (Cuadernos de Filología Clásica. Estudios Latinos, 2024)
This paper studies how the caricature character of Philaenis is created, presented as an ugly and one-eyed woman (2.33, 4.65, 10.22, 12.22) and as an active, androgynous and notably masculine tribad (7.67, 7.70, 9.29, 9.62). The culmination of the character comes in the epigram 9.40, where Philaenis promises her husband a spectacle of voyeurism, letting an innocent girl lick her vulva and vagina. Thus he goes from cunnilinctrix to irrumatrix and adopts, even without knowing it, the active and virile sexual role that she so longed for in 7.67. This character represents the archetype of a woman who crosses the limits, unable to control her passions and who confuses the scale of sexual values. Philaenis, who, with her masculinity, refuses to be penetrated, even orally, and tries to be only active, does not realize that by performing oral sex on women, she is still a fellatrix and becomes passive, thus becoming orally penetrated.